Answer:
Step-by-step explanation:
Convert mixed fraction to improper fraction.
Find LCM of the denominators and find equivalent fraction.
Now, subtract
[tex]7\dfrac{2}{9}=\dfrac{(7*9)+2}{9}=\dfrac{63+2}{9}=\dfrac{65}{9}[/tex]
[tex]5\dfrac{1}{5}=\dfrac{26}{5}[/tex]
LCM of 9 and 5 = 45
[tex]\dfrac{65}{9}*\dfrac{5}{5}=\dfrac{325}{45}[/tex]
[tex]\dfrac{26}{5}*\dfrac{9}{9}=\dfrac{234}{45}[/tex]
[tex]7\dfrac{2}{9}- 5\dfrac{1}{5}=\dfrac{65}{9}-\dfrac{26}{5}\\\\ =\dfrac{65*5}{9*5}-\dfrac{26*9}{5*9}\\\\\\=\dfrac{325}{45}-\dfrac{234}{45}\\\\\\=\dfrac{325-234}{45}\\\\\\=\dfrac{91}{45}\\\\\\=2\dfrac{1}{45}[/tex]